Effectiveness Stimulus Environment Problem Solving Learning Model for Increase High-level Thinking Skills - Kusumadani, Annur Indra; Rahmadani, Salsabila Nur; Halim, Ilham Surya (Journal of Biology Learning, 2024)
Learning with Stimulus Environment Problem Solving (SEPS) is an involved learning process student in a way active good in network nor outside network in reading, writing, doing experiment, and analyze, as well look for solution to the problem social related science environment public.  This study aims to know the effectiveness of the Stimulus Environment Problem Solving (SEPS) learning model so that can increase ability think level high among students biology education Universitas Muhammadiyah Surakarta. Method in study this is correlate ability think critical and solving problem 2 groups student a total of 40 students where is one group totaling 20 students use learning model of Stimulus Environment Problem Solving (SEPS) and other groups with Project based Learning. Analysis hypothesis using the t test and effect size. Based on application of the Stimulus Environment Problem Solving (SEPS) model in the classroom experiment experience increase in t test results significant in cycle I and cycle II. Based on the effect size test, the effectiveness of the Stimulus Environment Problem Solving (SEPS) model is included in category tall with value 3.244 so effectiveness of the Stimulus Environment Problem Solving (SEPS) model on Skills think level tall own category tall.